2018
DOI: 10.1016/j.jastp.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of decameter wavelength sky noise during x-ray solar flares in 2013–2017 based on the observations of midlatitude HF radars

Abstract: Based on a joint analysis of the data from 10 midlatitude decameter radars the effects are investigated during 80 x-ray flares in the period 2013-2017. For the investigation nine mid-latitude SuperDARN radars of the northern hemisphere (Adak Island West and East radars, Blackstone radar, Christmas Valley East and West radars, Fort Hays East and West radars, Hokaido East radar and Wallops radar) and Ekaterinburg coherent decameter radar of ISTP SB RAS are used. All the radars work in the same 8-20MHz frequency … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 26 publications
5
47
0
Order By: Relevance
“…Green sectors in Figures a–h correspond to the field of view of 16 radars that meet the criteria above and used to process the absorption data. As one can see, the obtained results demonstrate the dependence discussed earlier (Berngardt et al, )—the main noise absorption is most often observed in the sunlit region. On the other hand, it is clear that only part of the radars (about half) operates in a sufficient mode for measurement—on the one hand they do not significantly change the operating frequencies, on the other hand, they have a sufficiently high noise level to study its dynamics.…”
Section: Diagnostics Of Global Absorption Effectssupporting
confidence: 85%
See 4 more Smart Citations
“…Green sectors in Figures a–h correspond to the field of view of 16 radars that meet the criteria above and used to process the absorption data. As one can see, the obtained results demonstrate the dependence discussed earlier (Berngardt et al, )—the main noise absorption is most often observed in the sunlit region. On the other hand, it is clear that only part of the radars (about half) operates in a sufficient mode for measurement—on the one hand they do not significantly change the operating frequencies, on the other hand, they have a sufficiently high noise level to study its dynamics.…”
Section: Diagnostics Of Global Absorption Effectssupporting
confidence: 85%
“…The next important issue arising in the investigation of noise data by coherent radars is the interpretation of the detailed temporal dynamics of the noise absorption. As shown in Berngardt et al () and seen in Figures a–c, the front of noise absorption at the radar correlates well with the shape of the X‐ray flare according to GOES/XRS 1–8 Å . The rear is substantially delayed with respect to the X‐ray 1‐ to 8‐ Å flare.…”
Section: Correlation Of Absorption Dynamics With Solar Radiation Of Dsupporting
confidence: 77%
See 3 more Smart Citations